2019
DOI: 10.1088/1367-2630/ab145a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast dynamic evolution of multilevel systems in medium-strength laser fields

Abstract: The ultrafast dynamic evolution of an atomic system under medium-strength laser fields is studied by performing transient absorption measurement. An analytical model developed from perturbation theory with a modified transition dipole moment is presented to explain the spectral features of the multilevel system. By fitting the measured absorption spectra to the model, the system's dynamic evolution is quantified by different amplitude and phase modulation factors in the pump-probe and probe-pump scenarios. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A number of femtosecond 4WM experiments revealed that richer information on the photoinduced dynamics in atomic vapors, polyatomic chromophores, multichromophore aggregates, and nanosystems can be obtained by applying more intense laser pulses (see refs for reviews). On the theoretical side, a variety of simulations of 4WM signals beyond the limit of weak system–field coupling have been reported. ,,,, Single-molecule femtosecond spectroscopy of individual chromophores and antenna complexes , also usually requires strong pulses.…”
Section: Nonperturbative Calculation Of the Nonlinear Polarizationmentioning
confidence: 99%
“…A number of femtosecond 4WM experiments revealed that richer information on the photoinduced dynamics in atomic vapors, polyatomic chromophores, multichromophore aggregates, and nanosystems can be obtained by applying more intense laser pulses (see refs for reviews). On the theoretical side, a variety of simulations of 4WM signals beyond the limit of weak system–field coupling have been reported. ,,,, Single-molecule femtosecond spectroscopy of individual chromophores and antenna complexes , also usually requires strong pulses.…”
Section: Nonperturbative Calculation Of the Nonlinear Polarizationmentioning
confidence: 99%